Please solve the question given in the description

Asked by mac12303190 | 6th Jan, 2010, 08:38: PM

Expert Answer:

Dear Student


From figure   

Tan A= h/ (a+x)

Tan B=h/ (b+x)

We should get rid of X in the above equation

Tan A  Tan B=  h2 / (a+x)(b+x)   (1)

Tan A -Tan B= [ (b+x)h - (a+x)h  ] / [ (a+x)(b+x) ]  =(b-a)h /  [ (a+x)(b+x)] (2)

Equation (1)/(2)      (Tan A  Tan B) / (Tan A -Tan B) = h/(b-a)

   h=   [(b-a)Tan A  Tan B] / (Tan A -Tan B)



Answered by  | 7th Jan, 2010, 10:48: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.